EFEKTIVITAS PENERAPAN PEMBELAJARAN FISIKA BERBASIS MULTIREPRESENTASI UNTUK MELATIH KETERAMPILAN PROSES SAINS FISIKA SISWA MAN 1 PEKANBARU - Winda Muzdalifah Muzdalifah; Fakhruddin '; M. Rahmat ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This research aims to determine the effectiveness of implementation of physics learning by multiple representation through practicing students’ science process skills in lesson Newton’s law in class X IPA1 MAN 1 Pekanbaru. The subjects were students of class X IPA1 totalling 29 students, consisting of 8 male students and 21 female students. The instrument of data collection in this study is the process skills test consists of 8 essay questions. Analysis of the data in this study is a descriptive analysis to see an overview of the results of the students' learning skills by using the criteria of absorption, the effectiveness of learning, and students’ learning completeness. The analysis of the data showed: absorption class average is 81.68% with a good category, otherwise learning effectiveness declared in effective way, then completeness of learning’s students classically worth 86.21% and declared complete, completeness of lesson by 75% and declared incomplete. Nevertheless, it can be concluded that implementation of physics learning by multi representation is could be used in learning process class X IPA1 MAN 1 Pekanbaru. Key Words : multi representation, process skills, newton’s law